Seeing the Window, Finding the Spider: Applying Critical Race Theory to Medical Education to Make Up Where Biomedical Models and Social Determinants of Health Curricula Fall Short - Tsai, Jennifer; Lindo, Edwin; Bridges, Khiara (Frontiers in Public Health, 2021)
A professional and moral medical education should equip trainees with the knowledge and skills necessary to effectively advance health equity. In this Perspective, we argue that critical theoretical frameworks should be taught to physicians so they can interrogate structural sources of racial inequities and achieve this goal. We begin by elucidating the shortcomings in the pedagogic approaches contemporary Biomedical and Social Determinants of Health (SDOH) curricula use in their discussion of health disparities. In particular, current medical pedagogy lacks self-reflexivity; encodes social identities like race and gender as essential risk factors; neglects to examine root causes of health inequity; and fails to teach learners how to challenge injustice. In contrast, we argue that Critical Race Theory (CRT) is a theoretical framework uniquely adept at addressing these concerns. It offers needed interdisciplinary perspectives that teach learners how to abolish biological racism; leverage historical contexts of oppression to inform interventions; center the scholarship of the marginalized; and understand the institutional mechanisms and ubiquity of racism. In sum, CRT does what biomedical and SDOH curricula cannot: rigorously teach physician trainees how to combat health inequity. In this essay, we demonstrate how the theoretical paradigms operationalized in discussions of health injustice affect the ability of learners to confront health inequity. We expound on CRT tenets, discuss their application to medical pedagogy, and provide an in-depth case study to ground our major argument that theory matters. We introduce MedCRT: a CRT-based framework for medical education, and advocate for its implementation into physician training.